Methods of neocystourethroanastomosis formation in orthotopic bladder plastic surgery after radical cystectomy - P. S. Kozlova; K. M. Nyushko; V. A. Gorbach; B. Ya. Alekseev (Исследования и практика в медицине, 2020)
This literature review describes various surgical techniques that reduce the urinary incontinence chance after orthotopic plastic surgery of the bladder by Studer. Satisfactory retention of urine is possible in case of maintaining the maximum length of the urethra, consistency of vesico-urethral anastomosis, sufficient volume of neocystis with low pressure, as well as functional and morphological adaptation of the intestinal wall. The techniques that help to reduce tension in the region of the vesico-urethral anastomosis and pressure in a short mesentery, preservation of functional urethral length by "secondary sphincter" using, attention is paid to some exposure characteristics of the ileum segment of sufficient length for the formation of neocities a satisfactory amount of, performing neotestamentaria during robot-assisted of cystoplasty, comparing the surgical techniques, as well as possible the feasibility of using suture V‑loc. A modified method for forming a robot-assisted anastomosis for laparoscopic operations is described. The results of clinical studies are presented, in one of which the results of modification of the "non-hole" technique are considered, and in the other — the method of temporary tension of the anastomosis zone. The article describes the experience of forming a vesico-urethral anastomosis using a CAPIO cross-linking device, as well as the experience of reconstructing The denonvillier fascia intraoperatively. An artificial device to achieve urinary retention: the artificial urinary sphincter (AUS).